International reserve-holding in the developing world: self insurance in a crisis-prone era? - Mendoza, Ronald U (Archīum Ateneo, 2004)
Developing countries’ reserves have increased dramatically in recent years—growing by over 60% since the Asian financial crisis. This paper explores the self-insurance motivation behind this. As a first step, it revisits the literature on international reserve demand. This paper then examines the reserve-holding trends in a sample of 65 developing countries. It seeks to answer the following: Have reserves increased across the board or have these been concentrated in a few countries? If so, does it represent a break in previous policy? At what cost? This paper concludes by briefly examining some policy implications and avenues for future research.